2016
DOI: 10.3168/jds.2015-9892
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding whole compared with cell-free colostrum on calf immune status: Vaccination response

Abstract: Vaccination contributes to improved herd health and production. Boosting immune development at a young age may have long-term effects by enhancing vaccine immune response and efficacy. In the bovine, colostrum is the sole source of maternal immunity, having a substantial effect on health status in the neonate. To date, colostral antibody concentration is used to evaluate colostrum quality. However, colostrum also contains proteins and cells, which may affect immune development and future responses to vaccines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 38 publications
(47 reference statements)
0
11
0
3
Order By: Relevance
“…29,30 A recent study also suggested that maternal colostral cells had long-term effects on the development of the calf's immune system. 31 Calves that received whole colostrum had stronger responses to vaccination 6 to 10 months post-colostrum feeding as compared to calves fed cell-free colostrum. This observation suggests that these maternal cells may play a role in "training" or "priming" the developing immune system of the calf.…”
Section: Discussionmentioning
confidence: 91%
“…29,30 A recent study also suggested that maternal colostral cells had long-term effects on the development of the calf's immune system. 31 Calves that received whole colostrum had stronger responses to vaccination 6 to 10 months post-colostrum feeding as compared to calves fed cell-free colostrum. This observation suggests that these maternal cells may play a role in "training" or "priming" the developing immune system of the calf.…”
Section: Discussionmentioning
confidence: 91%
“…Except IgA, other nonspecific colostral compounds, such as lysozyme and lactoferrin, participate in the newborn immune response, even though they are considered of minor importance (Handl et al, 2009). In other domestic animals, white blood cells, such as macrophages, neutrophils and lymphocytes are other compounds of the PIT: these cells are able to cross the intestinal barrier and enhance neonatal immunity during the first month of life (Liebler-Tenorio et al, 2002;Langel et al, 2015Langel et al, , 2016. They release IgA locally when in contact with digestive pathogens (Wheeler et al, 2007).…”
Section: Local Passive Immune Transfermentioning
confidence: 99%
“…Vaccination is one of the most useful management practices to protect animals from different pathogens (Carrol and Forsberg, 2007), and conferring successful vaccine protection in cattle is important in preventing new or recurring infections (Langel et al, 2016). Antigens present in the vaccine stimulate the humoral response (i.e., antibody production) without causing disease (Kindt et al, 2007).…”
Section: Discussionmentioning
confidence: 99%